Educational management and student affairs programs of top performing schools - De Mesa, Rosalinda C. (2007)
This research aimed to study the profile of Student Affairs Program of the participating schools in relation to several academic management factors as well as the effectiveness of the management of student affairs programs and services. Quantitative data were obtained from two structured questionnaires while qualitative approach was done through the use of Student Affairs Program Checklist Questionnaire designed as an interview guide for CSAOs of UPD, PUP-Manila, and UST. It was found that student affairs professionals are active contributors to student learning, growth, and development. The participating schools have shown effectiveness based on the 7Ss Management Framework. Adoption of the Staff Associates Model developed by Barr, Desler, and Associated further strengthens the effectiveness of the student affairs management.
Thesis (M.A. Educational Administration)--University of the Philippines Diliman.
Keywords: Universities and colleges -- Philippines -- Manila Metropolitan Area -- Administration; School management and organization -- Philippines -- Manila Metropolitan Area; Student affairs services -- Philippines -- Manila Metropolitan Area; College student development programs -- Philippines -- Manila Metropolitan Area